THE ADOPTION OF CUSTOMER RELATIONSHIP MANAGEMENT IN THE SINGAPORE PHARMACEUTICAL INDUSTRY:FROM THE PERSPECTIVE OF RELATIONAL INFORMATION PROCESSES - Lam, Joyce (2007)
The pharmaceutical industry is in the midst of a challenging period. It is laden with critical issues such as increased research and development (R & D) cost, stiffer regulatory requirements, patent expirations, decreased R & D yield, public cost containment pressures, government interference and increasing media and public scrutiny. In this light, it is crucial for pharmaceutical (pharma) companies to adopt Customer Relationship Management (CRM) as a strategic initiative to improve sales and marketing effectiveness for sustainable growth.